Search for a heavy resonance decaying to a top quark and a vector-like top quark in the lepton + jets final state in pp collisions at √s = 13 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Nature, 2019)
A search is presented for a heavy spin-1 resonance Z decaying to a top quark and a vector-like top quark partner T in the lepton + jets final state. The search is performed using a data set of pp collisions at a centre-of-mass energy of 13 TeV corresponding to an integrated luminosity of 35.9 fb−1 as recorded by the CMS experiment at the CERN LHC in the year 2016. The analysis is optimised for final states arising from the T decay modes to a top quark and a Higgs or Z boson (T → Ht, Zt). The event selection makes use of resolved and merged top quark decay products, as well as decays of boosted Higgs bosons and Z and W bosons using jet substructure techniques. No significant deviation from the standard model background expectation is observed. Exclusion limits on the product of the cross section and branching fraction for Z → tT, T → Ht, Zt, Wb are presented for various combinations of the Z resonance mass and the vector-like T quark mass. These results represent the most stringent limits to date for the decay mode Z → tT → tHt. In a benchmark model with extra dimensions, invoking a heavy spin-1 resonance G∗, masses of the G∗ between 1.5 and 2.3 TeV and between 2.0 and 2.4 TeV are excluded for T masses of 1.2 and 1.5 TeV, respectively